Critical Experiential Learning in the Native American Community for Title IV-E Students: A Pilot Evaluation. Issue 3 (26th May 2016) - Johnston-Goodstar, Katie; Piescher, Kristine; LaLiberte, Traci
Abstract : This article describes the development, implementation of, and outcomes associated with a specialized seminar designed to increase contextual and historical knowledge necessary for work with Native American families in the child welfare system and to increase students' personal and professional growth in this capacity. Findings from a 2-year pilot evaluation revealed that students' knowledge significantly increased over time compared with that of their non-participating peers. Seminar participation also led to personal and professional growth. Findings suggest that critical experiential learning significantly enhances traditional pedagogy for graduate social workers preparing to work in child welfare, a field plagued with disparity.